Economic impact of milk price incentive scheme on dairy farming in Karnataka - HS, Sowmya; Kiran Kumar R Patil (Indian Journal of Dairy Science, 2024)
The present study attempts to examine the economic impact of milk price incentive scheme announced by Government of Karnataka on production, productivity and profitability of milk production in Karnataka. To assess the impact of scheme on production and productivity of milk, time series data on number of milch cows and buffaloes, production and productivity were collected from livestock census reports from 1997 to 2019. To examine its impact on profitability, pertinent information was elicited from 60 sample dairy farmers coming under the jurisdiction of SHIMUL, Karnataka. Exponential growth models, production function considering production/productivity as dependent variable and share of cross bred in total milch bovine population, dummy variable to capture the influence of scheme as independent variables and enterprise budgeting to examine profitability were employed.   The results indicated that number of indigenous milch cows and buffaloes have decelerated while that of cross bred cows have accelerated at a greater pace. Substantial and significant Milk production in case of cross bred cows was due to extensive production while in case of indigenous bovines it was mainly due to intensive production. The milk price incentive of Rs.5 per litre announced by Government in 2016 has increased milk production by 79.90 percent and productivity by 115  percent compared to milk production and productivity without milk incentive (prior to 2008). The share of cross bred cows have almost doubled after the implementation of the scheme. In terms of profitability, farmers will be under loss to the tune of Rs. 1.43 per litre of milk in the absence of milk incentive while they realize profit of Rs. 3.57 per litre with Rs. 5 per litre as incentive. Delay in the payment of incentive and its inability to keep the rising pace of growth in input prices are considered as the major lacuna of the scheme. Farmers have suggested for doubling the existing incentive to Rs. 10 per litre to absorb the shock of rising prices of inputs and to obtain sustainable profit from the enterprise.